2010
DOI: 10.1142/s0192415x10008007
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Imaging of Ginsenosides Localization in Panax ginseng Root

Abstract: We performed mass spectrometric imaging (MSI) to localize ginsenosides (Rb(1), Rb(2) or Rc, and Rf) in cross-sections of the Panax ginseng root at a resolution of 100 microm using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Tandem mass spectrometry (MS/MS) of alkali metal-adducted ginsenoside ions revealed structural information of the corresponding saccharides and aglycone. MALDI-MSI confirmed that ginsenosides were located more in the cortex and the periderm than that in the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Chemical analysis and immunological staining demonstrated that the root epidermis contains a high level of ginsenosides (Fukuda et al, 2006;Taira et al, 2010;Yokota et al, 2011). Furthermore, histochemical staining revealed the distribution of ginsenosides mainly in the oil canals in the periderm and outer cortex regions of the root, but not in the xylem or pith, the two zones which comprise most of the root (Christensen et al, 2006;Tani et al, 1981) (Fig.…”
Section: Cellular and Subcellular Locations For Synthesizing Ginsenosmentioning
confidence: 97%
“…Chemical analysis and immunological staining demonstrated that the root epidermis contains a high level of ginsenosides (Fukuda et al, 2006;Taira et al, 2010;Yokota et al, 2011). Furthermore, histochemical staining revealed the distribution of ginsenosides mainly in the oil canals in the periderm and outer cortex regions of the root, but not in the xylem or pith, the two zones which comprise most of the root (Christensen et al, 2006;Tani et al, 1981) (Fig.…”
Section: Cellular and Subcellular Locations For Synthesizing Ginsenosmentioning
confidence: 97%
“…To date a number of ionization techniques that belong to SALDI have been proposed,1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, ...…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles as typical, in treatable forms such as suspension liquids in order to ensure that the photon energies of the laser can act to desorp and ionize analytes 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. Indeed, the soft ionization laser method such as the original form of MALDI also belongs to this category 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As other representative plant food samples, Panax ginseng 20 and Capsicum fruit 21 are well known as natural medicines as well as food products. Many pharmacological properties of glycoside ginsenoside and the alkaloid capsaicin have been reported.…”
Section: Concept For Food Analysis By Mass Spectrometry Imaging (Msi)mentioning
confidence: 99%